Analyzing the Role of Digital Transformation and Innovation in Business Strategy and Performance - Amisa Fatel Samosir; Dwi Lestari; Citra Agung; Brian Seva Sitanggang; Kurnia Asa; Kuswanto Kuswanto; Dwi Rayana Siregar; Novita Sari Br Simanjuntak (The Future of Education Journal, 2026)
Digital transformation and innovation have become strategic elements that determine organizational competitiveness across various business sectors. This study aims to comprehensively analyze how digital transformation and innovation affect business strategy and performance over the past 3–5 years, map current trends, identify research gaps, and develop a conceptual framework linking digital transformation, innovation, and organizational performance. The method used is a Systematic Literature Review (SLR) of 25 articles to systematically identify trends, key findings, and research gaps. The synthesis results show that digital technology not only improves operational efficiency but also opens opportunities for new product, service, and business model innovation. The integration of artificial intelligence (AI), data analytics, and digital platforms enables companies to respond to market changes quickly and based on data, making business strategies more adaptive and predictive. The success of digital transformation is influenced by a combination of internal factors (organizational culture, human resource capacity, cross-departmental collaboration, and digital marketing capability) and external factors (regulation, technology access, market conditions, and consumer preferences). This study provides practical implications for managers and business decision-makers in designing an adaptive and sustainable digital transformation strategy.